Management of internal disc derangement using normal saline and sodium hyaluronate: A comparative study - Neha Singh; Shailendra Kumar Dubey; Nilesh Bhanawat; Gaurav Rai; Abhishek Kumar; Ritesh Vatsa (Wolters Kluwer Medknow Publications, 2021)
Background: Arthrocentesis of the temporomandibular joint (TMJ) is the unadorned form of surgical therapy which comprises of lavage of inflammatory enzymes and mediators and improve joint mobility and eliminate pain by pressure of the lavage solution in the upper compartment of TMJ. Objectives: The current study was conducted to assess and compare the effectiveness of arthrocentesis with normal saline alone and in conjunction with sodium hyaluronate (SH) injection in the treatment of internal derangement of the TMJ. Methodology: Sixty patients with internal derangement of the TMJ were randomly divided into two equal groups; Group 1 was performed with normal saline and Group 2 with normal saline followed by 1 ml of SH. The patients were followed up after 1 week to check for any postoperative complications and 1, 2, and 3 months for subsequent sessions and changes in subjective and objective variables. Results: The increase in mouth opening from preoperative to 3 months' postoperatively was 4.9 mm for Group 1 and 6.43 mm for Group 2. The change in the pain score (visual analogue scale scale) in Group 1 from the preoperative session to 3 months' follow-up was 7.23-4.1 and in Group 2 was 7.36-3.7. The difference in clicking/popping in Group 1 from preoperative session to 3 months' follow-up was 2.43-1 and in Group 2 was 2.4-0.53. Conclusion: Patients refractory to conservative treatment showed promising results with arthrocentesis with SH than arthrocentesis alone in treatment of TMJ internal derangement.